AB0360 Impact of Abatacept on Disease Activity and Functional Status in Patients with Different Duration of Rheumatoid Arthritis. (15th July 2016) - Kanonirova, M.A.; Lukina, G.; Sigidin, Y.; Aronova, E.; Glukhova, S.; Luchihina, E.; Karateev, D.; Nasonov, E.
Abstract : Background: Abatacept (ABA) is a selective co-stimulation modulator, which is widely used in treatment of RA. There isn't enough data about its effectiveness and impact on functional status in patients with early (ERA) and long-standing (LS) rheumatoid arthritis (RA). Objectives: To assess the impact of ABA on disease activity and functional status in patients with different duration of RA. Methods: 85 patients (pts) with active RA and an inadequate response to synthetic DMARDs or biologics were enrolled in the study. They were grouped into 2 arms based on RA duration: less than three years (early RA) and more than three years (LS RA), i.e. 51% and 49% pts in each group, respectively. Most of them were middle aged females (48, 8±13, 5 years) with high disease activity (DAS28=5, 25±1, 15), RF-positive (76, 7%) and ACPA-positive (73, 1%). ABA (10 mg/kg) was administered intravenously following the adult intravenous dosing regimen. Disease activity was assessed by DAS28, functional status by HAQ-DI and results by EULAR criteria every 12 weeks. Results: Before treatment DAS28 in ERA pts was 5, 1±0, 9, in LS RA – 5, 3±1, 3 and HAQ-DI in ERA pts was 1, 3±0, 6, in LS RA - 1, 6±0, 9. In three months after ABA therapy initiation a significant improvement in DAS28 and HAQ-DI was achieved in both groups ( p <0, 05). Improvement by EULAR response criteria was registered in 80% of pts with ERA and 67% of pts with LS RA. There was no significant difference between two groups after 3 and 6 months of treatment in achieving a good EULAR response: 27, 5% and 43, 75% – in early RA pts, 28, 57% and 38, 4% – in LS RA pts. There was a comparable percentage of non-responders after 3 and 6 months of therapy in both groups (at 3 months – 20% in early RA group, 31, 4% – in LS RA group; at 6 months – 18, 7% and 19, 2% respectively). After 3 months and 6 months the improvement of HAQ-DI in ERA group was significantly higher, than in LS RA group (p<0.05). 28 adverse events (AEs) in 17 (20%) pts were registered. The most frequent AE were upper respiratory tract infections – 10 (11, 8%) pts. Serious AEs (SAEs) occurred in 4 (4, 7%) pts. Conclusions: ABA has shown significant improvement in reduction of disease activity and improvement in functional status in pts with RA. No significant difference was seen between the groups of ERA and LS RA by EULAR criteria. However, pts in ERA group had significant improvement of HAQ-DI comparing with LS RA group. ABA has good safety profile, adverse events were registered only in 20% of patients. Disclosure of Interest: None declared